New additions to the Chinese Agraeciini Redtenbacher, 1891 (Orthoptera, Tettigoniidae: Conocephalinae) with report the complete mitochondrial genome of Palaeoagraecia brunnea Ingrisch, 1998 - Liu, Jing; Luo, Haiyu; Lu, Xiangyi; Bian, Xun (Zootaxa, 2021)
This paper reports one newly recorded species and one new species from China, namely Anelytra (Lichnofugia) symfioma (Ingrisch, 1998) and Liara (Liara) shii Liu & Bian sp. nov. All the species of Agraeciini Redtenbacher, 1891 from China are listed. The examined specimens are deposited in Guangxi Normal University. The complete mitochondrial genome of Palaeoagraecia brunnea Ingrisch, 1998 was 15984 bp and consisted of 37 genes and a control region. The A + T content of the mitogenome was as high as 70.2%. Most protein-coding genes started with the codon ATN and ended with typical stop codons TAA. Phylogenetic analyses based on mitogenomes suggested that Palaeoagraecia brunnea and the genus Pseudorhynchus had the closest genetic relationship.